PENGETAHUAN, KETERAMPILAN, PENGAWASAN INTERNAL, KOMITMEN DAN AKUNTABILITAS PENGELOLAAN KEUANGAN KOTA BENGKULU - Melinda, Rekha (UNIB Press, 2019)
This research aims to examine the effect of knowledge, skill, internal supervision, to the accountability of regional financial management areas on the regional work units in bengkulu city goverment. Populations used in this research are all OPD Bengkulu City. The research data was obtained through questionnaire given to the Head of Unit, head of financial sub-division, treasurer of expenditure and treasurer of receipt. The result shows that knowledge, skill, internal supervision has a positive and significant effect of the accountability to regional financial management.